2019
DOI: 10.1007/s00193-018-00885-w
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the limitation of geometrical shock dynamics for diffraction over wedges

Abstract: Geometrical Shock Dynamics (GSD) is a simplified model for nonlinear shock wave propagation for which the front evolution is governed by a local relation between the geometry of the shock and its velocity, so-called A − M rule. Numerous studies have proven the ability of the GSD model to estimate correctly the leading shock front in interaction with obstacles. Nevertheless, a solution for the problem of diffraction over a convex corner does not always exist, especially for weak shocks. To overcome this limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Slight discrepancies, such as underestimation of the triple point trajectories, may be imputed to the non conservativity of the model formulation. In the future we plan to extend our method to weak shocks following the Lagrangian idea developed in [1], and to develop a conservative high order formulation to improve the computational efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Slight discrepancies, such as underestimation of the triple point trajectories, may be imputed to the non conservativity of the model formulation. In the future we plan to extend our method to weak shocks following the Lagrangian idea developed in [1], and to develop a conservative high order formulation to improve the computational efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The need to develop a method for rapidly calculating the mechanical effects of shocks is, however, of prime importance in many applications such as the prevention of industrial accidents and the computation of structure loading, or the definition of source models for acoustic propagation codes. Recent researches have shown that a promising solution [1,2] could be envisaged thanks to the Geometrical Shock Dynamics model (GSD).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since only a limited number of shock dynamics problems can be solved analytically using GSD, many algorithms were developed to numerically implement GSD models including front tracking methods [6,[10][11][12][16][17][18][19][20], finite difference [5] and finite volume schemes [21,22] based on the conservation form of GSD, and a recent level-set fast marching approach [23]. Among these schemes, the front tracking-based Lagrangian schemes appear to be the most popular ones that have been used for a wide range of shock dynamics problems since accuracy and speed can be well balanced.…”
Section: Methodsmentioning
confidence: 99%